High-Isolation wideband MIMO antenna with offset T-Shaped slots for 5G/WLAN applications - Chen, Shuyi; Lu, Na; Sun, Jiaxing; Zhou, Changfei; Li, Changxian; Wu, Di (Frontiers in Physics, 2022)
A broadband multiple-input multiple-output (MIMO) antenna with high isolation operating in 3.14-5.42 GHz (2.28 GHz, 53.3%) is proposed for 5G smartphone. An offset T-shaped slot with dual functions is employed to improve the bandwidth of one antenna element and enhance the isolation. Then, the double L-shaped stubs are loaded to improve the impedance matching of the other antenna in the MIMO antenna. Finally, the 2×2 MIMO antenna is constructed by four T-shaped monopole antennas, two double L-shaped stubs, and two offset T-shaped slots. The proposed MIMO antenna is first simulated and then experimentally tested with a good agreement. High isolation of greater than 15 dB, high antenna efficiency of more than 54%, and low envelope correlation coefficient (ECC) of smaller than 0.08 are realized within 3.14-5.42 GHz. These good performances indicate that the proposed antenna can be applied for MIMO applications in smartphones.